Collaborative Strategy for Building Sustainable Economic Independence in Gandasoli Village through the Establishment of the Merah Putih Village Cooperative - Teti Rahmawati; Rizki Indrawan; Siti Nuke Nurfatimah (Jurnal Sentra Pengabdian, 2025)
This community service program aimed to build sustainable economic independence in Gandasoli Village, Kuningan Regency, through the establishment of the Merah Putih Village Cooperative. Despite having abundant natural and human resources, the village lacked an economic institution capable of managing local potential collectively. In response to Presidential Instruction No. 9 of 2025 on village cooperatives, the program was implemented using a participatory and collaborative approach involving Universitas Kuningan, the Gandasoli Village Government, and local communities. The activities included socialization, training, technological innovation, mentoring, and evaluation. The results showed significant outcomes: increased community understanding of cooperative principles (up 36% from pre-test to post-test), completion of all legal and organizational documents, and successful integration of simple digital tools that improved administrative transparency and member participation. The cooperative now serves as a formal village economic institution fostering inclusiveness, transparency, and accountability. Beyond institutional establishment, the program strengthened social capital, enhanced local economic literacy, and created a model of sustainable community-based development. This initiative demonstrates that university–government–community collaboration can effectively accelerate the achievement of Sustainable Development Goals (SDGs), particularly in promoting decent work, economic growth, and poverty reduction